2018
DOI: 10.1111/eci.12951
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase activation in neutrophils: Role of the phosphorylation of its subunits

Abstract: Neutrophils are key cells of innate immunity and during inflammation. Upon activation, they produce large amounts of superoxide anion (O ) and ensuing reactive oxygen species (ROS) to kill phagocytized microbes. The enzyme responsible for O production is called the phagocyte NADPH oxidase. This is a multicomponent enzyme system that becomes active after assembly of four cytosolic proteins (p47 , p67 , p40 and Rac2) with the transmembrane proteins (p22 and gp91 , which form the cytochrome b ). gp91 represents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
176
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(182 citation statements)
references
References 70 publications
4
176
0
2
Order By: Relevance
“…To confirm the role of p47 phox and Nox2 in MVS-induced responses, the protein levels of p47 phox and Nox2 were knocked down by their respective siRNAs and reduced the MVS-induced HO-1 expression in HPAEpiCs ( Figure 4C). Previous studies have shown that phosphorylation of p47 phox leading to NADPH oxidase/ROS-dependent HO-1 expression could protect against the release of inflammatory mediators from HPAEpiCs [19,34]. First, we found that MVS-stimulated phosphorylation of p47 phox was reduced by transfection with p47 phox siRNA ( Figure 5A).…”
Section: P47 Phox -Dependent Nox/ros Generation Is Required For Mvs-isupporting
confidence: 50%
“…To confirm the role of p47 phox and Nox2 in MVS-induced responses, the protein levels of p47 phox and Nox2 were knocked down by their respective siRNAs and reduced the MVS-induced HO-1 expression in HPAEpiCs ( Figure 4C). Previous studies have shown that phosphorylation of p47 phox leading to NADPH oxidase/ROS-dependent HO-1 expression could protect against the release of inflammatory mediators from HPAEpiCs [19,34]. First, we found that MVS-stimulated phosphorylation of p47 phox was reduced by transfection with p47 phox siRNA ( Figure 5A).…”
Section: P47 Phox -Dependent Nox/ros Generation Is Required For Mvs-isupporting
confidence: 50%
“…According to the literature, infiltrated leukocytes in tissues and their PMNs generate ROS in several ways. ROS production is stimulated by the generation of superoxide anions by phagocyte NADPH oxidase (Belambri et al, ), which is mediated by protein kinase C and raf‐MEK‐ERK activation (Awasthi et al, ). In addition, signals from PMNs result in the release of granule proteases, and the secreted effectors trigger ROS production (Glennon‐Alty, Hackett, Chapman, & Wright, ).…”
Section: Discussionmentioning
confidence: 99%
“…ROS production depends on the activation of NADPH oxidase, an enzymatic system that transfers electrons from cytosolic NADPH to phagolysosomal O 2 to produce superoxide anion (O 2 − ). NADPH oxidase activation leads to respiratory burst, which consists of increased oxygen consumption by neutrophils . In the resting cell, some NADPH oxidase components, such as p40 phox , p47 phox , and p67 phox exist as a complex in the cytosol.…”
Section: Introductionmentioning
confidence: 99%